Viola Davis e a jornada da compaixão: uma psicobiografia à luz da terapia focada na compaixão afrocentrada - Andrade, Emanuelle Oliveira (2024)
Psychobiography is a research method that aims to explore and integrate art, psychology and biography, seeking to understand the complexity of the human personality, through the systematic study of the individual lives of public figures (Schultz, 2005). Exploratory, descriptive and dialogical in nature, psychobiography is traditionally based on psychological theories and requires the use of cross-cultural and multidisciplinary research practices that enable the integrative examination of individual lives within sociocultural and historical contexts. The present study draws on selected European and African psycho-philosophical perspectives, anchored in Compassion Focused Therapy (Gilbert, 2024) and African Philosophies (Wedderburn, 2007; Nobles, 2009; Oyěwùmí, 2021; Somé, 2003; Diop, 2014 and others) with the intention of fostering dialogue and facilitating cross-cultural psychological understanding, since African and CFT perspectives are rarely considered as psychological lenses in psychobiography. This single case study is a life analysis of 58-year-old American actress Viola Davis, an African-American actress, businesswoman, producer, and philanthropist. Viola Davis is a descendant of two generations of people who were enslaved. She is an African-American woman and public figure who bore the triple burden of inequality (social, racial and gender). Today, she has become one of the most celebrated black actresses in history and the third woman to win the EGOT title, the main awards in American entertainment. Viola was selected through intentional sampling due to the publication of her autobiography Finding Me (2022), in which she spoke about systemic-intergenerational and biographical traumas experienced since childhood and which are directly related to the social context, the result of a complex and disregarded African history. Primary, secondary, tertiary sources and other selected publicly available artistic productions/performances were used and data extraction was guided by some of Alexander's (1990) salience indicators through a reinterpretation in light of the cognitive unconscious. The results demonstrate the relevance of a holistic understanding of Viola Davis' personality development, shedding light on aspects of the biopsychosocial mind, emphasizing the role of social mindsets, context, and the construction of a compassionate self, which she was able to use and strengthen despite all adverse conditions. Compassion for one's own and others' pain and suffering can be seen as weakness and for the weak, and thus care has little or no place. Identifying and understanding the impact of racism on Viola Davis' life trajectory was essential for understanding her Journey so far (1964 - 2024). Like many black women in history, Viola also went on a Journey to Heal, to recover her ability to be human, to speak, to express herself, to be seen, heard, and to occupy her true place in the world, similar to what happened in The Woman King, in her most recent artistic production. As a Black woman, now 58, Viola seems to live her life intentionally as an act of protest, and she says we must come together to promote Healing. Our community, past, present, and future, is counting on this.